How should teams be formed and managed? - Hideo Owan (IZA World of Labor, 2014)
The keys to effective teamwork in firms are (1) carefully designed team-formation policies that take into account what level of diversity of skills, knowledge, and demographics is desirable and (2) balanced team-based incentives. Employers need to choose policies that maximize the gains from teamwork through task coordination, problem solving, peer monitoring, and peer learning. Unions and labor market regulations may facilitate or hinder firmsâ attempts at introducing teams and team-based incentives.
Keywords: D23; J16; J24; J33; L2; M5; 330; job design; team; diversity; team-based incentives; task assignment; peer effect